2021
DOI: 10.1111/tpj.15377
|View full text |Cite
|
Sign up to set email alerts
|

Ferredoxin 1 is downregulated by the accumulation of abscisic acid in an ABI5‐dependent manner to facilitate rice stripe virus infection in Nicotiana benthamiana and rice

Abstract: Summary Ferredoxin 1 (FD1) accepts and distributes electrons in the electron transfer chain of plants. Its expression is universally downregulated by viruses and its roles in plant immunity have been brought into focus over the past decade. However, the mechanism by which viruses regulate FD1 remains to be defined. In a previous report, we found that the expression of Nicotiana benthamiana FD1 (NbFD1) was downregulated following infection with potato virus X (PVX) and that NbFD1 regulates callose deposition at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 115 publications
0
20
0
Order By: Relevance
“…In the present study, we found that IP‐L could inhibit the expression of NbCML30 at the nucleic acid and protein levels (Figure 5a–j). We speculate that on the one hand, IP‐L may induce the production of some viral siRNAs, leading to the targeted degradation of NbCML30 mRNA, or IP‐L regulates some transcription factors to inhibit the transcription of NbCML30 (Cui et al., 2021); on the other hand, IP‐L directly interacts with NbCML30 and promotes its degradation through the 26S proteasome pathway. TMV infection inhibits NbCML30 expression, and this inhibition was suppressed after IP‐L silencing (Figures 2b and 5b).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found that IP‐L could inhibit the expression of NbCML30 at the nucleic acid and protein levels (Figure 5a–j). We speculate that on the one hand, IP‐L may induce the production of some viral siRNAs, leading to the targeted degradation of NbCML30 mRNA, or IP‐L regulates some transcription factors to inhibit the transcription of NbCML30 (Cui et al., 2021); on the other hand, IP‐L directly interacts with NbCML30 and promotes its degradation through the 26S proteasome pathway. TMV infection inhibits NbCML30 expression, and this inhibition was suppressed after IP‐L silencing (Figures 2b and 5b).…”
Section: Discussionmentioning
confidence: 99%
“…Yet, for virus infections including CaMV, the role of ABA appears complex. Increased ABA content was measured in Nicothiana tabacum after TMV infection (Whenham et al ., 1986),in rice after Rice stripe virus infection (Cui et al ., 2021), and Cucumber mosaic virus (Alazem et al ., 2014), but not PPV infection in Arabidopsis thaliana (Pasin et al ., 2020). Further treatment with ABA increased plant resistance to Tobacco mosaic virus (Chen et al ., 2013), Plum pox virus (Pasin et al ., 2020), Chinese wheat mosaic virus (He et al ., 2021) and Bamboo mosaic virus (BaMV) in Arabidopsis (Alazem et al ., 2014) as well as reduced the lesion size in local infections of Tobacco necrosis virus (TNV) (Iriti & Faoro, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Stress responses are highly dynamic and dependent on stress severity, as evidenced by the strikingly small overlap between transcriptome profiles under mild and severe stress in Arabidopsis (Clauw et al, 2015). Thus, under mild stress, priming-like responses might predominate, while under higher levels of salt stress, changes in ABA signalling might shift the balance towards viral susceptibility (Cui et al, 2021). This, alone, or in combination with other factors in the complex host defence network might result in the observed increase in PepMV RNA levels in plants maintained under high salinity compared to those maintained under low salinity.…”
Section: Pepmv-rdrpmentioning
confidence: 99%
“…ABA has been found to promote an antiviral response and induce resistance to potyviruses, either following exogenous application or in transgenic plants that overproduce ABA (Pasin et al, 2020). Another recent study, however, indicates a negative role for ABA, as its accumulation facilitates rice stripe virus infection in Nicotiana benthamiana and rice via down‐regulation of ferredoxin 1 (Cui et al, 2021). As key phytohormones act as major signalling molecules in triggering plant defence mechanisms, here, we examined the transcript levels of tomato SA‐, JA‐, ethylene (ET)‐ and ABA‐related genes under three soil salinity regimes (no‐added salt, low and high) in the absence or presence of pepino mosaic virus (PepMV), which is responsible for severe losses in tomato crops globally.…”
Section: Introductionmentioning
confidence: 99%